2011
DOI: 10.4155/fmc.11.4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 2D Fingerprints for Scaffold Hopping

Abstract: Universities of LeedsMethods. This paper reports a detailed evaluation of the effectiveness of six common types of 2D fingerprint when they are used for scaffold hopping similarity searches of MDDR, WOMBAT and MUV data.Results. The results demonstrate that 2D fingerprints can be used for scaffold hopping, with novel scaffolds being identified in nearly every search that was carried out. The degree of enrichment depends on the structural diversity of the actives that are being sought, with the greatest enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 29 publications
(36 reference statements)
2
56
0
1
Order By: Relevance
“…to have a higher scaffold-hopping potential. 36,37 This was confirmed previously for HTS-fingerprint similarity search by Petrone et al 7 Here, we investigated it in the context of machine learning. The diversity of scaffolds was assessed by calculating the distribution of Morgan3 similarities between the training actives and the actives in the first 5% test molecules, as well as by calculating the number of Bemis− Murcko scaffolds (BMS) 9 in the first 5% of the test molecules.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…to have a higher scaffold-hopping potential. 36,37 This was confirmed previously for HTS-fingerprint similarity search by Petrone et al 7 Here, we investigated it in the context of machine learning. The diversity of scaffolds was assessed by calculating the distribution of Morgan3 similarities between the training actives and the actives in the first 5% test molecules, as well as by calculating the number of Bemis− Murcko scaffolds (BMS) 9 in the first 5% of the test molecules.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…This characteristic of the coefficient was investigated in a subsequent study by Holliday et al who showed that a related similarity coefficient, the cosine coefficient, was less dependent on the precise nature of the weighing scheme that was being employed and that it was, accordingly, to be preferred if weighted fingerprints were to be used for similarity searching. [25] The weighting-scheme studies summarised here are just one aspect of the work we have conducted on 2D similarity searching over the past decade: other studies have included inter alia an investigation of the extent to which fingerprint-based similarity measures can be used for scaffold-hopping applications, [26] the use of reduced graphs for similarity searching as described further below, similarity searching using Bayesian inference networks, [27] a detailed comparison of the characteristics of different similarity coefficients that can be used with binary fingerprints, [28] and our work on data fusion, as discussed in the next section.…”
Section: Similarity-based Virtual Screeningmentioning
confidence: 99%
“…60 ECFP4 fingerprints 61 were used for all similarity calculations of compounds. The Tanimoto coefficient 62 was used as the measure of similarity between compounds.…”
Section: Similarity Calculationsmentioning
confidence: 99%